The Anthropologist and the Article - Reid, Bill (Culture, 1984)
For some reasons, most of the people, particularly anthropologists who write about the supernatural creatures of the Pacific Northwest Coast mythology, employ, to my way of thinking, a most peculiar dictional device: the dropping of the article which should ordinarily precede their specific names: e.g. “Raven” instead “the raven”. I have always found this practice most irritating and was eventually driven to write this paper. In doing so, I may have discovered that my argument goes deeper than a mere matter of style and touches on something fundamental regarding the attitude of today’s society to tribal peoples and their cultures.